2018
DOI: 10.1080/10717544.2018.1486472
|View full text |Cite
|
Sign up to set email alerts
|

A novel redox/pH dual-responsive and hyaluronic acid-decorated multifunctional magnetic complex micelle for targeted gambogic acid delivery for the treatment of triple negative breast cancer

Abstract: Gambogic acid (GA) is a naturally derived potent anticancer agent with extremely poor biocompatibility. In the present study, a novel of redox/pH dual-responsive multifunctional magnetic complex micelle (sPEG/HA/CSO-SS-Hex/Fe3O4/GA), which consisted of a reducible hexadecanol-modified chitosan oligosaccharide polymer micelle (CSO-SS-Hex) coated with hyaluronic acid (HA) and DCA grafted sheddable PEG-PLL (sPEG) copolymers and loaded with gambogic acid (GA) and Fe3O4 nanoparticles were developed for parenteral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The synthesis method for the hexadecanol-dithiodipronionic acid monoester (Hex-SS-Cy7) followed the method described in the literature 45. The SPION and Srfn loaded CSO-SS-Cy7-Hex/SPION/Srfn complex self-assemblies were prepared by dialysis, as reported previously 46. Figure 1 panel (A) shows the shell structure of CSO-SS-Cy7-Hex, and the scheme for the preparation of CSO-SS-Cy7-Hex/SPION/Srfn complex self-assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis method for the hexadecanol-dithiodipronionic acid monoester (Hex-SS-Cy7) followed the method described in the literature 45. The SPION and Srfn loaded CSO-SS-Cy7-Hex/SPION/Srfn complex self-assemblies were prepared by dialysis, as reported previously 46. Figure 1 panel (A) shows the shell structure of CSO-SS-Cy7-Hex, and the scheme for the preparation of CSO-SS-Cy7-Hex/SPION/Srfn complex self-assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…91 Monomethylpoly(ethylene glycol)-poly(e-caprolactone)-poly (trimethylene carbonate) (MPEG-P(CL-ran-TMC)) was used to encapsulate GA, which showed superior antitumor efficacy and a better apoptosis induced effect in AsPC-1 cells compared to free GA. 92 N-octyl-N-arginine-chitosan (OACS) micelles prepared by the dialysis method were utilized for GA oral delivery, which increased solubility by 2320 times and several folds of absorption compared with GA. 93 Besides, GA was encapsulated into the novel redox/pH dual-responsive and HA-decorated multifunctional magnetic complex micelles possessing excellent bioavailability, controllable release and multi-functionality, which could be an effective and promising strategy for the treatment of triple negative breast cancer. 94 Ke et al applied lecithin/solutol HS15 via the film-dispersion method to prepare the multilayer micelle employing protamine (PRM) and HA to deliver GA (HA-PRM-GA-M) for cancer treatment of inhibiting drug resistance. The results suggested that HA-PRM-GA-M showed the significant antitumor efficacy and tumor growth inhibitory effects without obvious histological abnormalities or hematological toxicity in the liver and kidney.…”
Section: Nano-scale Drug Delivery Systemsmentioning
confidence: 99%
“…Besides, GA was encapsulated into the novel redox/pH dual-responsive and HA-decorated multifunctional magnetic complex micelles possessing excellent bioavailability, controllable release and multi-functionality, which could be an effective and promising strategy for the treatment of triple negative breast cancer. 94 Ke et al applied lecithin/solutol HS15 via the film-dispersion method to prepare the multilayer micelle employing protamine (PRM) and HA to deliver GA (HA-PRM-GA-M) for cancer treatment of inhibiting drug resistance. The results suggested that HA-PRM-GA-M showed the significant antitumor efficacy and tumor growth inhibitory effects without obvious histological abnormalities or hematological toxicity in the liver and kidney.…”
Section: Nano-scale Drug Delivery Systemsmentioning
confidence: 99%
“…The targeted delivery of GA to TNBC is far less studied. The reported studies mainly use NP carriers to deliver GA to non-TNBC breast cancer (34)(35)(36). For example, a study used MDA-MB-231 cells, MCF-7 breast cancer cell lines, and 4T1 cell-bearing mice as models to study the anti-cancer effect of the co-delivery of GA and TNF-related apoptosis-inducing ligand (TRAIL) plasmid by hyaluronic acid grafted PEI-PLGA nanoparticles (GA/ pTRAIL-HA/PPNPs) (37).…”
Section: Discussionmentioning
confidence: 99%
“…Body weight variation is one of the parameters in toxicity testing. 34 Supplementary Figure S3A showed the body weight of the mice in different groups during the course of the treatments, which had no apparent difference between groups. Percentages of the changes in body weight were also calculated, that is the % difference of the body weight of each mouse between day 6 and day 17.…”
Section: Np-ga Has Lower Off-target Side Effectmentioning
confidence: 99%